Increased longevity of resins based composite restorations and their adhesive bond: a literature review - Gustavo Moncada; Patricio Vildósola; Eduardo Fernández; Juan Estay; Osmir B. De Oliveira-Junior; Javier Martin (Universidad de Antioquia, 2015)
Introduction: the goal of this literature review is to analyze the findings included in the literature concerning different alternatives to increase longevity of resin-based composite restorations and their adhesive bond. Method: bibliographies in the EBSCO database (Elton B Stephens Company) were reviewed using the following key words: "composite repair bond strength"; "restorations sealing"; composite restorations longevity"; "restorations refurbishment"; "composite bond strategy"; "dental adhesive collagen cross linking"; "proanthocyanidin dentin bond strength"; "multiple layer dentin bond strength", and "dentin adhesive evaporation bond strength". Clinical and laboratory results were analyzed in terms of repairing, sealing, and refurbishing defective restorations, in addition to improvements in impregnation of adhesive surfaces, resistance of adhesive polymers, and the progress recently made concerning resistance to hydrolytic collagen degradation. Results: repairing, sealing, or refurbishing defective restorations allow keeping tooth structure healthy, reducing potential damage to dental pulp, as well as operatory pain, often caused without anesthetics. New bonding management techniques provide adhesive procedures with increased longevity. Conclusions: repairing, refurbishing, or sealing defective composite resins increase the longevity of restorations and restored teeth by using minimally invasive dental techniques. Other methods, such as improving impregnation of adhesive surfaces, increasing adhesive polymers strength, and hydrolytic degradation of collagen are promising advances that modify the management of bonding techniques, providing patients with restorative treatments of increased longevity.